PERTUMBUHAN MISELIUM Trichoderma sp. PADA LIMBAH CAIR TEMPE DAN LIMBAH AIR KELAPA - Juliana Juliana; Umrah Umrah; Asrul Asrul (Biocelebes, 2017)
The purpose study was to determine potential tempe industry liquid waste and coconut water waste as medium propagation miselium Trichoderma sp. The treatment was conducted based on completely randomized design, consisting of seven treatments and three replication, namely: P0 (control), P1 (tempe industry liquid waste 100%), P2 (tempe industry liquid waste 80% + coconut water waste 20%), P3 (tempe industry liquid waste 60% + coconut water waste 40% ), P4 (tempe industry liquid waste 40% + 60% coconut water waste), P5 (tempe industry liquid waste 20% + 80% coconut water waste), P6 (100% coconut water waste). Variable observation included are media pH formula and the weight of mycelium biomass Trichoderma sp. The results showed that Trichoderma sp. Can be grown on all treatments except treatments P0 (control). The treatments produced in the highest mycelium biomass is P3 : 1595,333 mg per 100 mL medium, and this not significantly different from P2 : 1566,667 mg, but significantly different with all treatments.